Examination of weighting for the protectionof the fundamental rights of children (2014)
The rights of children have been instituted as fundamental principles in international human rights treaties. The Colombian Constitution, in its Article 44 says: “the children ́s rights take precedence over the rest”. It is necessary to practice the modern theory of weighting of the principles in collision, as this will be the only method to establish the need, reasonableness and proportionality of the slaughter inflicted on a fundamental principle that determine a conditional precedence relation, for which the interpreter must undergo a review of constitutionality of the highest rigor of hermeneutical type. Likewise, the interpreter must make a rigorous examination when there is a collision of fundamental principles of reinforced and prevalent protection as in the case of collision between the fundamental rights of two or more children, where he should pursue the benefit in accordance with the law.